Facticity of Existence and Cultivation of a Wisdom - Petrović, Aleksandar (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Achievements of ones’ working life are significant in marking and rounding off one’s own 70th anniversary of life. This paper present the basic avenues of interpretation of the concept of time in Husserl, Heidegger, and Fink in the historical thinking, taking into consideration the subtle objections presented by Milan Uzelac in his three-part study of the phenomenology of our time as the end of the historical process. His insights are authentic and deliberate by topology.